Interactive Digital Module Development For Mathematical Representation Skills Using A Contextual Learning Approach - Nugroho Noto Priatmajo; Fertilia Ikashaum (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
The need for technology-based teaching materials that align with online learning environments has significantly increased in the past two years. This shift has led to the transition from traditional teaching resources to digital learning materials. This study aims to develop an interactive digital module focused on statistical material by contextualizing students' representational skills. The development process followed a design research methodology with a development study approach, which included preliminary and formative evaluations—namely self-evaluation, prototyping, and field testing. The participants of this study were eighth-grade students from Middle School 3 Metro. Data were collected using observation sheets, interviews, and student assessments. The results indicated that the interactive digital module met the